Mental State Talk Structure in Children's Narratives: A Cluster Analysis. (21st March 2017) - Pinto, Giuliana; Primi, Caterina; Tarchi, Christian; Bigozzi, Lucia
Abstract : This study analysed children's Theory of Mind (ToM) as assessed by mental state talk in oral narratives. We hypothesized that the children's mental state talk in narratives has an underlying structure, with specific terms organized in clusters. Ninety-eight children attending the last year of kindergarten were asked to tell a story twice, at the beginning and at the end of the school year. Mental state talk was analysed by identifying terms and expressions referring to perceptual, physiological, emotional, willingness, cognitive, moral, and sociorelational states. The cluster analysis showed that children's mental state talk is organized in two main clusters: perceptual states and affective states. Results from the study confirm the feasibility of narratives as an outlet to inquire mental state talk and offer a more fine-grained analysis of mental state talk structure.